Decomposing general equilibrium effects of policy intervention in multi-regional trade models: method and sample application - Christoph Böhringer; Thomas F. Rutherford (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
Policy interventions in large open economies do not only affect the allocation of domestic resources but change international market prices. The change in international prices implies an indirect secondary burden or benefit for all trading countries. This secondary terms of trade effect may have important welfare implications: Countries without change in domestic policies may nevertheless gain or suffer from the action of other countries; in turn, the primary welfare effect of countries interfering domestically may be substantially enhanced or weakened due to international spill-overs. Obviously, policy makers of economies that are integrated into international markets have an essential interest to gain insights about the different sources of welfare changes associated with domestic policy changes. In this paper, we present a decomposition that splits the overall welfare effect into a domestic market effect holding international prices constant and an international market effect as a result of changes in international prices (terms of trade effect). We demonstrate the usefulness of our decomposition approach in the context of an empirical welfare analysis of international carbon abatement policies.
Keywords: 330; Wirtschaftspolitik; Klimaschutz; Außenwirtschaftstheorie; Allgemeines Gleichgewicht; Wohlfahrtseffekt; Internationaler Preiszusammenhang; Theorie; OECD-Staaten